1993
DOI: 10.1091/mbc.4.9.897
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen and p21 are components of multiple cell cycle kinase complexes.

Abstract: We have recently shown that two proteins, proliferating cell nuclear antigen (PCNA) and p21, are associated with cyclin D. Here we show that PCNA and p21 are common components of a wide variety of cyclin/cyclin-dependent kinase complexes in nontransformed cells. These include kinase complexes containing cyclin A, cyclin B, and cyclin D, associated either with CDC2, CDK2, CDK4, or CDK5. We show that PCNA and p21 form separate quatemary complex with each cyclin/CDK and that these quatemary complexes contain a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
217
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(225 citation statements)
references
References 62 publications
7
217
0
1
Order By: Relevance
“…Studies indicated that p21 interacts with the proliferating cell nuclear antigen (PCNA). This p21/ PCNA interaction could inhibit the process of DNA synthesis, which is a major process in DNA damage repair, leading to an arrest in the G 2 -M phase (40)(41)(42). Moreover, we found that lower concentration of dual PI3K/mTOR inhibitors alone slightly induced apoptosis.…”
Section: Discussionmentioning
confidence: 67%
“…Studies indicated that p21 interacts with the proliferating cell nuclear antigen (PCNA). This p21/ PCNA interaction could inhibit the process of DNA synthesis, which is a major process in DNA damage repair, leading to an arrest in the G 2 -M phase (40)(41)(42). Moreover, we found that lower concentration of dual PI3K/mTOR inhibitors alone slightly induced apoptosis.…”
Section: Discussionmentioning
confidence: 67%
“…Among these factors there are negative regulators of cell growth, the CDK inhibitors (CDIs). Expression of one of them, p21 (WAF1/CIP1/CDKN1), a universal component of cyclin-CDK complexes (Zhang et al, 1993), is frequently abolished by mutational or viral inactivation of its positive regulator p53 in many tumors (ElDeiry et al, 1993;Hollstein et al, 1991). A key role in the regulation of S-phase entry of a cell is played by the product of the Rb tumor suppressor gene pRB.…”
Section: Introductionmentioning
confidence: 99%
“…PCNA forms a quaternary complex with CDK, cyclin D, and p21, suggesting that PCNA may play an important role in cell cycle regulation beyond its function in the DNA replication machinery (13)(14)(15). CDKs regulate progression through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%